Chloroplast genome of the wild tuber-bearing diploid potato relative Solanum chacoense. Issue 2 (12th December 2017) - Cho, Kwang-Soo; Choi, Jang-Gyu; Cho, Ji-Hong; Im, Ju-Sung; Park, Young-Eun; Hong, Su-Young; Park, Tae-Ho
Abstract: Solanum chacoense is a wild tuber-bearing species belonging to Solanaceae family. The chloroplast genome of the species was completed by de novo assembly using a small amount of whole genome sequencing data. The genome is the circular DNA molecule with a length of 155, 532 bp containing 159 predicted genes totally, including 105 protein-coding, 45 tRNA and eight rRNA genes. Maximum-likelihood phylogenetic analysis with 26 species in Solanaceae revealed that S. chacoense is the most closely grouped with S. commersonii .